The Effect of Meat and Bone Meal (MBM) on Crop Yields, Nitrogen Content and Uptake, and Soil Mineral Nitrogen Balance - Anna Nogalska (MDPI AG, 2021)
A long-term (six year) field experiment was conducted in Poland to evaluate the effect of meat and bone meal (MBM), applied without or with mineral nitrogen (N) fertilizer, on crop yields, N content and uptake by plants, and soil mineral N balance. Five treatments were compared: MBM applied at 1.0, 1.5, and 2.0 Mg ha−1, inorganic NPK, and zero-fert check. Mineral N accounted for 100% of the total N rate (158 kg ha−1) in the NPK treatment and 50%, 25%, and 0% in MBM treatments. The yield of silage maize supplied with MBM was comparable with that of plants fertilized with NPK at 74 Mg ha−1 herbage (30% DM) over two years on average. The yields of winter wheat and winter oilseed rape were highest in the NPK treatment (8.9 Mg ha−1 grain and 3.14 Mg ha−1 seeds on average). The addition of 25% and 50% of mineral N to MBM had no influence on the yields of the tested crops. The N content of plants fertilized with MBM was satisfactory (higher than in the zero-fert treatment), and considerable differences were found between years of the study within crop species. Soil mineral N content was determined by N uptake by plants rather than the proportion of mineral N in the total N rate. Nitrogen utilization by plants was highest in the NPK treatment (58%) and in the treatment where mineral N accounted for 50% of the total N rate (48%).